Quantum phase shifts and interference effects in multisolenoidal and multitoroidal systems - Palangao, Marinell B. (Institute of Physics, College of Science, University of the Philippines Diliman, 2015)
The AB phase shifts due to a single solenoid and a single toroid are calculated. This is done using two methods - the first method involves explicit calculation of fluxes due to magnetic fields, while the second method requires direct evaluation involving the magnetic vector potential. The phase shifts and interference patterns involving two parallel solenoids of a three slit electron interference configuration and two co-axial and two co-planar toroids of two slit electron interference configurations are then determined. It is shown that the presence of electromagnetic fluxes, in regions enclosed by interference paths, shifts the observed intensity patterns. It is also observed that changing the direction of the currents also shifts the intensity patterns.